تحديد مستوى حوكمة تكنولوجيا المعلومات المطبق في المصرف التجاري السوري باللاذقية وفق إطار عمل (COBIT) - زيود, لطيف; علي, حسين; نصور, ريم محمد (Latakia University Journal - Economic and Legal Sciences Series, 2014)
يهدف البحث إلى تحديد مستوى حوكمة تكنولوجيا المعلومات المتوفرة في المصرف التجاري السوري باللاذقية باستخدام نموذج (COBIT) بأبعاده الأربعة: التخطيط والتنظيم, الاكتساب والتنفيذ, الدعم والتوصيل, المتابعة والتقييم. اعتمد البحث على منهج المسح الإحصائي, وذلك من خلال استقصاء آراء الإداريين في المصرف التجاري السوري لمعرفة مستوى تطبيق حوكمة تكنولوجيا المعلومات بالاستناد إلى نموذج COBIT, وهو أداة تستخدم للرقابة على تكنولوجيا المعلومات. طوّر بواسطة معهد حوكمة تكنولوجيا المعلومات في الولايات المتحدة الأمريكية عام 1992, ويحدد نموذج العمل هذا (34) هدف ذو مستوى عال للرقابة على عمليات تكنولوجيا المعلومات, كما يوفّر هذا الإطار معياراً عاماً قابلاً للتطبيق, ومقبولاً من أجل أمان جيد لتكنولوجيا المعلومات, وممارسات للرقابة من أجل تدعيم احتياجات الإدارة في تحديد المستوى المناسب لتأمين تكنولوجيا المعلومات ومتابعته, كما يزود مدققي الحسابات بمجموعة من القياسات, والمؤشرات المقبولة للحصول على حوكمة جيدة تساعدهم في ابداء رأيهم في المؤسسة. تمّ توزيع (43) استبانة على الإداريين المسؤولين في المصرف التجاري السوري باللاذقية, وتمّ استرجاع /40/ استبانة كاملة وصالحة للتحليل الإحصائي, وبلغت نسبة الاستجابة 93.02%. وتوصل البحث إلى أن مستوى تطبيق حوكمة تكنولوجيا المعلومات في المصرف التجاري السوري باللاذقية وفق إطار عمل (COBIT) بأبعاده الأربعة هو مستوى متوسط. وأوصت الباحثة بضرورة أن يتم تطبيق نموذج لقياس حوكمة تكنولوجيا المعلومات للمصارف التجارية السورية, وذلك وفق نموذج (COBIT), ليكون مقياساً معيارياً لمستوى حوكمة تكنولوجيا المعلومات, ومساعداً لهذه المصارف لمعرفة الوضع الراهن لديها. The research aims to determine the level of governance of information technology available in the Commercial Bank of Syria Latakia using a form (COBIT) four dimensions: planning and organization, acquisition and implementation, delivery and support, monitoring and evaluation. The research on the survey methodology, and through the survey of administrators in the Commercial Bank of Syria to determine the level of application of IT governance model based on COBIT, a tool used for the control of information technology. Developed by the Institute of IT governance in the United States in 1992, and defines the business model of this (34) goal with a high level of control over the IT operations, it also provides the framework general standard applicable and acceptable for good security for information technology, and practices for the control of to strengthen the management needs to identify and follow up to ensure the appropriate level of information technology, also provides auditors set of measurements, and accepted indicators for good governance to help them give their opinion in the organization. Were distributed (43) The identification of the administrative officials of the Commercial Bank of Syria Latakia, was retrieved / 40 / identification of a complete and valid for statistical analysis, the response rate was 93.02%. The research found that the level of application of IT governance in the Commercial Bank of Syria Lattakia according to the framework (COBIT) is the four dimensions of the average level. The researcher recommended that it should be applied to measure model IT Governance Syrian commercial banks, according to model (COBIT), to be the yardstick for the level of IT governance, and an assistant to the banks to find out the status quo has.